PENERAPAN PRINSIP MODEL VIEW CONTROLLER PADA SISTEM INFORMASI DOSEN BERBASIS WEBSITE: IMPLEMENTATION OF THE MODEL VIEW CONTROLLER PRINCIPLE IN A WEB-BASED FACULTY INFORMATION SYSTEM. - Rizal Fadia Al Fikri; Euis Hernawati (LPPM Universitas Abdurrab, 2024)
institutions. This research aims to develop a web-based Faculty Information System at Politeknik Piksi Ganesha. This system is designed to enhance efficiency and effectiveness in managing faculty data, research, and community service. Currently, data management relies on Microsoft Excel, which is susceptible to data loss and damage. In developing this system, the Software Development Life Cycle (SDLC) method and the Model-View-Controller (MVC) as the primary architecture are employed. The Model is responsible for providing and manipulating data from the database, the View displays information to the user, and the Controller manages tasks performed by the Model and View. With the existence of this system, it is expected to provide a centralized solution for faculty data management, reduce the risk of data loss, and facilitate information control. The results of this research include the development of an application that can improve the efficiency of faculty data management at Politeknik Piksi Ganesha. The conclusion of this research highlights the positive potential of the information system that can significantly contribute to enhancing the quality of educational services. The implementation of this Faculty Information System is expected to support the improvement of the faculty information management process in this institution.